Pengaruh ROM Pasif Terhadap Laju Pernapasan Dan SpO2 Pada Pasien Post Craniotomy Di ICU RSUD Dr. Moewardi Surakarta Tahun 2015 - Nopitasari Nopitasari; Endang Caturini Sulistyowati (Poltekkes Kemenkes Surakarta, 2017)
Abstract : Passive ROM, Respiration Rate, Oxygen Saturation, Post Craniotomy Patient, ICU. Patient with bedrest condition will have inteference of muscle streght, its needed implementation to reduce. One of them is medic rehabilitation ROM (Range of Motion) by active and passive movement. One of purpose of ROM Passive on critical patient in ICU is to stable cardiovascular function, respiration and oxygen saturation. To know the effect of passive ROM to respiration rate and oxygen saturation on post craniotomy patient in ICU RSUD Dr. Moewardi. The research using pre eksperimental design. Desain using One Group pre-post test design. Sample on the research using purposive sampling and 30 respondences. Result research of passive ROM to respiration rate have been gotten data there are changes respiration rate before and after, have enhancement 3,967. Data oxygen saturation before and after 1,333. There are effect passive ROM to respiration rate and oxygen saturation.